Character sums with exponential functions and their applications - Koni͡agin, S. V. (Sergeĭ Vladimirovich) (Cambridge tracts in mathematics, 1999)
The theme of this book is the distribution of integer powers modulo a prime number. It provides numerous new links between number theory and computer science as well as other areas of mathematics. Applications include (but are not limited to) complexity theory, random number generation, cryptography, and coding theory.